Ketika Pers Bicara Korupsi: Analisis Tajuk Rencana Harian Pedoman pada Awal Orde Baru 1969 – 1974 - Padiatra, Aditia Muara (UI Scholars Hub, 2015)
This article discusses the role of the press in uncovering cases of corruption, using the editorial of Pedoman daily newspaper in the early years of the New Order period 1969-1974. The newspaper was eventually prohibited to publish because of its stand to oppose the authoritarian Soekarno government. At the time of president Soeharto’s New Order, the newspaper was allowed to run again, but was officially banned in January 1974 because of the publication of the students’ demonstration in the Malari or Malapetaka Lima Belas Januari opposing the government welcoming the Japanese companies operating in Indonesia. At both the Soekarno and Soeharto governments, Rosihan Anwar was the chief editor of Pedoman. The content analysis will also refer to Indonesia Raya newspaper, which like Pedoman, was suppressed not to criticize the government. The newspaper was no longer free to express its opinion after the graft case in three key offices, Bulog (the National Logistics Agency), Pertamina (the state-owned national oil company), Bea Cukai (the Directorate General of Customs and Excise), and the police force, were exposed. The press was finally co-opted with the government rules.